Gud, evolution och ateism - Mikael Stenmark (Svensk Teologisk Kvartalskrift, 2013)
The past thirty years have seen an explosion of work applying evolutionary theory and related biological theories to ethics, sexes, racial issues, religion and many other topics that fall outside of biology as normally circumscribed. Many of these scholars are advocates of a Darwinian worldview. In this essay I critically discuss one group of Darwinists who claims that after Darwin atheism or naturalism is the only serious option for honest and scientifically-informed persons or at least that such persons do not believe that God is the creator of the world and that humans are made in the image of God. I try to show that these arguments are invalid and unconvincing, and I suggest instead that Christian faith or theism may offer support to science, which atheism or naturalism cannot provide.